Fidaxomicin compared with vancomycin and metronidazole for the treatment of Clostridioides (Clostridium) difficile infection: A network meta-analysis. Issue 1 (January 2020) - Okumura, Hiroyuki; Fukushima, Ayako; Taieb, Vanessa; Shoji, Shingo; English, Marci
Abstract: We conducted a systematic review of the literature and network meta-analysis (NMA) to compare the relative effectiveness of antibiotic treatments for Clostridioides ( Clostridium ) difficile infection (CDI) including vancomycin (VCM), metronidazole (MTZ) and fidaxomicin (FDX). Eligible studies were randomised controlled trials (RCTs) including adults with any severity of CDI that was treated with VCM, MTZ or FDX. The NMA was performed using a Bayesian framework, using a fixed-effects model. The searches identified seven publications for inclusion, which provided five RCTs for VCM versus MTZ, and three RCTs for FDX versus VCM. The NMA showed that for clinical cure rate, there was no difference for FDX versus VCM, and there was a significant difference in favour of FDX versus MTZ (odds ratio [OR]: 1.77; 95% credible interval [CrI] 1.11, 2.83]). For recurrence rate, there was a significant difference in favour of FDX versus both VCM (OR: 0.50; 95% CrI: 0.37, 0.68) and MTZ (OR: 0.44; 95% CrI: 0.27, 0.72). For sustained cure (clinical cure without recurrence), there was a significant difference in favour of FDX versus VCM (OR: 1.61; 95% CrI: 1.27, 2.05) and MTZ (OR: 2.39; 95% CrI: 1.65, 3.47). These findings suggest that FDX and VCM are effective first-line treatments for mild or moderate CDI, whereas MTZ is not, and FDX may be more effective at preventing CDI recurrence than VCM.